From Counting Wars to Accounting for Peace: Implications for Economic Growth in Nigeria - Wisdom Okere; Oluwakemi Towolawi; Cynthia Uloma Okere (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2023)
This study examined the effect of Peace Accounting on Economic Growth in Nigeria. The study adopted an ex post facto research design for a period of 30 years (1991-2020). Descriptive and inferential statistics were used to analyze the gathered data. The degree of relationship among variables was analyzed using Error Correction Model (ECM) after preliminary analyses were done such as the unit root test and Johansen co-integration because of the use of Time series data. The results show that at a significance level of five per cent, the data demonstrated a significant and positive correlation between the two variables. In addition, the findings of the research indicate that there is a substantial and favourable correlation between the independent factors (Peace accounting) in Nigeria and the dependent variables (Economic growth) in Nigeria. The study thereby recommends that there should be an increase in government recurrent expenditure to cover defence infrastructures in the economy as well as fund activities and programs that will directly improve the lives of the people. It also recommends that exposing corrupt actions, maintaining openness and accountability in the public sector, and preventing dishonest acts might help lower the high rate of corruption.